2002
DOI: 10.1017/s135561770281325x
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception without awareness in a patient with posterior cortical atrophy: Impaired explicit but not implicit processing of global information

Abstract: A patient with progressive posterior cortical atrophy (PCA) was examined on several tests of visual cognition. The patient displayed multiple visual cognitive deficits, which included problems identifying degraded stimuli, attending to two or more stimuli simultaneously, recognizing faces, tracing simple visual stimuli, matching simple shapes, and copying objects. The patient was also impaired in identifying visual targets contained at the global level within global–local stimuli (i.e., smaller letters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 84 publications
1
15
0
1
Order By: Relevance
“…Mackenzie Ross et al [23] and Galton et al [11] proposed dividing PCA into subtypes, which are distinguishable at onset but tend to merge as the disease progresses: (A) predominantly occipito-temporal with visual agnosia, (B) predominantly parietal with deficits of visuo-spatial cognition and (C) a "primary visual failure" subtype with early visual-perceptual deficits. Seven of our cases can be assigned to subtype B (2 to 6,8,9). One of them had additional early disturbances of vision and developed hemianopia (no.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mackenzie Ross et al [23] and Galton et al [11] proposed dividing PCA into subtypes, which are distinguishable at onset but tend to merge as the disease progresses: (A) predominantly occipito-temporal with visual agnosia, (B) predominantly parietal with deficits of visuo-spatial cognition and (C) a "primary visual failure" subtype with early visual-perceptual deficits. Seven of our cases can be assigned to subtype B (2 to 6,8,9). One of them had additional early disturbances of vision and developed hemianopia (no.…”
Section: Discussionmentioning
confidence: 92%
“…2). Nestor et al [26] observed similar hypometabolism in frontal areas related to the control of eye movements (Brodman areas 6,8). As they pointed out, this finding may represent a remote effect due to deafferentation, caused by the degeneration of projecting fiber from posterior visual association areas.…”
Section: ■ Imaging Findingsmentioning
confidence: 85%
See 1 more Smart Citation
“…As noted, there are a few reports of “implicit” visual processing in the setting of dorsal visual stream dysfunction (Coslett & Saffran, 1991; Coslett et al, 1995; Filoteo et al, 2002; Stark et al, 1997; Wojciulik & Kanwisher, 1998). The most recent of these was a case study reported by Filoteo and colleagues (2002).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have most often been motivated by questions of levels of visual awareness: If ''neglected'' distractors interfere with per-ceptual processing or motor responses, then patients must process them implicitly, even when explicit recognition is impaired (66)(67)(68)(69)(70)(71)(72)(73). The focus of these studies has been to investigate whether equivalent distractor interference effects might be obtained with intact vs. damaged parietal cortex.…”
mentioning
confidence: 99%